TINJAUAN FIQH MUAMALAH TERHADAP PEMAKAIAN SISTEM PAY LATER DALAM APLIKASI JUAL BELI ONLINE SHOPEE - Witry Octasary Aritonang (Program Studi Ekonomi Syariah, 2022)
In the era of technology that continues to develop over time, online services are created to meet the needs of human life, making all the necessities of life easy to fulfill, such as one of the online buying and selling services in an application called Shopee. from food, clothing, to household appliances and others, and for users of this application, it is no stranger to one of the systems offered by Shopee to pay for purchased goods, where Shopee makes the